2016
DOI: 10.1200/jco.2016.34.15_suppl.e20523
|View full text |Cite
|
Sign up to set email alerts
|

Use of dedicated gene panel sequencing using next generation sequencing to improve the personalized care of lung cancer.

Abstract: Advances in Next Generation Sequencing (NGS) technologies have improved the ability to detect potentially targetable mutations. However, the integration of NGS into clinical management in an individualized manner remains challenging. In this single-center observational study, we performed a dedicated NGS panel studying 41 cancer-related genes in 50 consecutive patients with metastatic non-small-cell lung cancer between May 2012 and October 2014. Molecular analysis could be performed in 48 patients with a good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Specifically, our panel were composed of 21 genes including ALK, AKT1, BRAF, CDKN2A, DDR2, ERBB2, EGFR, FGFR1, FGFR2, IDH1, KRAS, MAP2K1, MET, NRAS, PDGFRA, PIK3CA, PTEN, RET, ROS1, STK11 and TP53, which had mutation frequency above 1% in the lung cancer samples of COSMIC database, and 17 genes of them were identified as oncogenes and the other 4 genes were identified as tumor suppressor genes by OncoKB database (Figure 1). Moreover, we overlapped the 21-gene panel with other 4 previously published NSCLC sequencing panel which have similar size to ours (24)(25)(26)(27), the overlapping results indicated that our panel has not only shared core driver genes (TP53, EGFR, PIK3CA, etc.) with them, but also uniquely covered some clinically important genes (DDR2, ROS1, IDH1, etc.…”
Section: The Establishment Of the Nsclc Target Sequencing Panel Clini...supporting
confidence: 57%
“…Specifically, our panel were composed of 21 genes including ALK, AKT1, BRAF, CDKN2A, DDR2, ERBB2, EGFR, FGFR1, FGFR2, IDH1, KRAS, MAP2K1, MET, NRAS, PDGFRA, PIK3CA, PTEN, RET, ROS1, STK11 and TP53, which had mutation frequency above 1% in the lung cancer samples of COSMIC database, and 17 genes of them were identified as oncogenes and the other 4 genes were identified as tumor suppressor genes by OncoKB database (Figure 1). Moreover, we overlapped the 21-gene panel with other 4 previously published NSCLC sequencing panel which have similar size to ours (24)(25)(26)(27), the overlapping results indicated that our panel has not only shared core driver genes (TP53, EGFR, PIK3CA, etc.) with them, but also uniquely covered some clinically important genes (DDR2, ROS1, IDH1, etc.…”
Section: The Establishment Of the Nsclc Target Sequencing Panel Clini...supporting
confidence: 57%
“…Molecular tumor boards (MTBs) have been developed at multiple academic medical centers to address physician barriers to precision medicine, providing guidance on the use of NGS reports. [18][19][20][21][22] Importantly, availability of an MTB increases physician willingness to order and use NGS testing. 23 MTBs are generally composed of a multidisciplinary team including medical oncologists, surgical oncologists, genetic counselors, pathologists, pharmacists, radiologists, and basic scientists, 19,21 working together to provide recommendations to clinicians for targeted therapy and clinical trials on the basis of each patient's diagnosis and NGS results.…”
Section: Especially In Rural and Medicallymentioning
confidence: 99%
“…The idea of the MTB has been a growing treatment paradigm in the field of precision oncology with variable success in clinical practice [21,22,24,25]. For example, some MTBs have demonstrated objective response rates as high as 44–67% in patients with non‐small cell lung cancer [26,27]. However, other MTBs treating various solid and hematologic cancers have shown objective response rates from 0–13% [28,29].…”
Section: Introductionmentioning
confidence: 99%